Employees’ Information Exchanges in Virtual Groups and Their Belief in Rumors and Their Dissemination in Cyberspace: Information Cascade Approach and Group Polarization - Morteza Moradi; Rabeah Zandipak (فرایند مدیریت و توسعه, 2021)
Purpose: The spread of internet and social networks has increased the number and speed of online rumors. In order to take more effective measures to deal with the negative effects of rumors, researchers and organizations must be aware of the main mechanism of online rumor transmission. This study is performed to investigate the employees’ information exchanges in virtual groups and their belief in rumors and their dissemination in cyberspace according to the information waterfall approach and group polarization. Methodology: In order to collect data, survey method and data analysis of correlation type were used. The statistical population of the study included the managers and employees of Hamedan Products Distribution Unit of the Oil Company, from among whom a sample size of 236 were determined. Findings: The results of path analysis show that the volume of arguments has a positive and significant effect on consistency with the arguments. Consistency with arguments has a positive and significant effect on the change of belief caused by arguments. The volume of arguments and consistency both have a positive and significant effect on belief in rumors.  Change in belief resulting from arguments and belief in rumors respectively affect belief in rumors and intention to disseminate rumors positively and significantly. Consistency with arguments plays a mediating role in the relationship between the volume of arguments and belief in rumors. Argument-induced change in belief plays a mediating role in the relationship between consistency with arguments and belief in rumors. Rumor anxiety plays a moderating role in the relationship between belief in rumors and intention to spread rumors.